Insecticide Resistance in Sitophilus zeamais Mots. and Rhizopertha dominicav (F.) in Indonesia - Osman, Noorma; Rejesus, B. Morallo (1985)
Fourteen strains of Sitophilus zaemais and fifteen strains of Rhizopertha dominica, collected from rice warehouses andfarmers' storage facilities throughout Indonesia were tested for resistance to malathion and pirimzphos methyl. Two strains of S. zeamais showed a slightly resistant response to malathion, while all strains of this species were susceptible to pirimzphos methyl. Resistance of R. dorninica to malathion was detected in three out of the fifteen strains tested. The predominant species of Sitophilus was S. zeamais.